Moving Beyond the Pillars of Cancer Treatment: Perspectives From Nanotechnology - Siamof, Cerise M.; Goel, Shreya; Cai, Weibo (Frontiers in Chemistry, 2020)
Nanotechnology has made a significant impact on basic and clinical cancer research over the past two decades. Owing to multidisciplinary advances, cancer nanotechnology aims to address the problems in current cancer treatment paradigms, with the ultimate goal to improve treatment efficacy, increase patient survival and decrease toxic side-effects. The potential for use of nanomedicine in cancer targeting and therapy has grown, and is now used to advance the four traditional pillars of cancer treatment: surgery, chemotherapy, radiation therapy and the newest pillar, immunotherapy. In this review we provide an overview of notable advances of nanomedicine in improving drug delivery, radiation therapy and immunotherapy. Potential barriers in the translation of nanomedicine from bench to bedside as well as strategies to overcome these barriers are also discussed. Promising preclinical findings highlight the translational and clinical potential of integrating nanotechnology approaches into cancer care.